2022
DOI: 10.3390/ijerph191710885
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Women’s Sexual and Reproductive Health at the Street Outreach Office

Abstract: The aim of study was to understand care strategies for homeless women, focusing on aspects of sexual and reproductive health from the perspective of Street Outreach Office strategy professionals. This is a qualitative study carried out in a large city in the countryside of São Paulo, Brazil. Data were collected from December 2020 to April 2021 through semi-structured interviews, and the results were obtained through content analysis and thematic modality. Nine health professionals participated in this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…For instance, studies reported on the importance of ‘trust’ for women to feel safe with a HCP and only then would they feel comfortable to disclose the extent of their issues [ 15 , 55 , 59 , 60 , 63 , 77 , 85 ]. Conversely, several studies capturing HCPs’ experiences reported that they were fully aware trust was an essential requirement to provide optimal care to women [ 57 , 72 , 75 , 80 83 , 90 , 91 ]. Continuity of care provider was often mentioned by HCPs and women as a pre-requisite to build a relationship of trust and honesty [ 49 , 75 , 80 83 , 85 , 89 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, studies reported on the importance of ‘trust’ for women to feel safe with a HCP and only then would they feel comfortable to disclose the extent of their issues [ 15 , 55 , 59 , 60 , 63 , 77 , 85 ]. Conversely, several studies capturing HCPs’ experiences reported that they were fully aware trust was an essential requirement to provide optimal care to women [ 57 , 72 , 75 , 80 83 , 90 , 91 ]. Continuity of care provider was often mentioned by HCPs and women as a pre-requisite to build a relationship of trust and honesty [ 49 , 75 , 80 83 , 85 , 89 91 ].…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were published between 1993 and 2024, with study settings predominantly in the Global North, including Cananda (n = 4) [ 52 55 ], Germany (n = 1) [ 56 ], United States of America (n = 16) [ 50 , 51 , 57 – 74 ], United Kingdom (n = 7) [ 9 , 49 , 75 80 ] and Australia (n = 12) [ 13 , 15 , 81 89 ]. One study was carried out in Brazil [ 90 ]. Nine studies included both women’s and HCPs’ views, twenty-two studies focused on women’s perspectives only and ten studies focused on HCPs’ perspectives only.…”
Section: Methodsmentioning
confidence: 99%
“…Addressing STIs prevention needs of homeless women can be enhanced through the integrating sexual health, and other health references services to homeless population [ 1 ]. A Brazilian study has found that gynecological care and sexual and reproductive health care in a Street Outreach Office represent an opportunity for welcoming and comprehensive care to the women being assisted, allowing the identification and care of the health needs and different demands of this population [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The social environment of the streets is complex, stigmatizing and permeated by gender-based power imbalances [ 5 , 6 ]. In this context, women are subject to violence, sexual exploitation, rape, prostitution, reproductive disorders, and a greater risk of sexually transmitted infections (STI) and unintended pregnancy, contributing to the perpetuation of the cycle of poverty and misery, in addition to unsafe abortion practices [ 6 9 ]. Among their numerous deprivations on the streets, sex can be configured as a means of meeting the subsistence needs of these women in a context of marginalization [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation